Advances in food and nutrition research. - Taylor, Steven L. (Advances in food and nutrition research., 2006)
Advances in Food and Nutrition Research recognizes the integral relationship between the food and nutritional sciences and brings together outstanding and comprehensive reviews that highlight this relationship. Contributions detail the scientific developments in the broad areas of food science and nutrition are intended to ensure that food scientists in academia and industry as well as professional nutritionists and dieticians are kept informed concerning emerging research and developments in these important disciplines. *Series established since 1948 *Advisory Board consists of 8 respected scientists *Unique series as it combines food science and nutrition research.